2022
DOI: 10.1039/d1sc03496k
|View full text |Cite
|
Sign up to set email alerts
|

How well does molecular simulation reproduce environment-specific conformations of the intrinsically disordered peptides PLP, TP2 and ONEG?

Abstract: Understanding the conformational ensembles of intrinsically disordered proteins and peptides (IDPs) in their various biological environments is essential for understanding their mechanisms and functional roles in the proteome, leading to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 87 publications
1
9
0
Order By: Relevance
“…Therefore we carried forward our analysis with a structure‐based balanced force‐field CHARMM36m 31 that generates structural, dynamics, and thermodynamic properties of a protein system with better accuracy. Moreover, CHARMM36m is an ideal force field for all‐atoms MD simulations because of its ability to show better correlation between the MD simulated and experimental data as well as reproduce the conformational transitions of solvent‐soluble as well as membrane peptides/proteins 86 . There are hundreds of available crystal structures of SARS‐CoV‐2 M PRO solved at different temperatures; however, they lack detailed comparative study of their molecular descriptions of the structure and its dynamics in aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore we carried forward our analysis with a structure‐based balanced force‐field CHARMM36m 31 that generates structural, dynamics, and thermodynamic properties of a protein system with better accuracy. Moreover, CHARMM36m is an ideal force field for all‐atoms MD simulations because of its ability to show better correlation between the MD simulated and experimental data as well as reproduce the conformational transitions of solvent‐soluble as well as membrane peptides/proteins 86 . There are hundreds of available crystal structures of SARS‐CoV‐2 M PRO solved at different temperatures; however, they lack detailed comparative study of their molecular descriptions of the structure and its dynamics in aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, CHARMM36m is an ideal force field for all-atoms MD simulations because of its ability to show better correlation between the MD simulated and experimental data as well as reproduce the conformational transitions of solvent-soluble as well as membrane peptides/proteins. 86 There are hundreds of available crystal structures of SARS-CoV-2 M PRO solved at different temperatures; however, they lack detailed comparative study of their molecular descriptions of the structure and its dynamics in aqueous solution. The dependency of structures on temperature has been vividly studied by many researchers, to acquire a better structure that will be relevant for molecular docking studies.…”
Section: Dynamics Of Catalytic Site Residuesmentioning
confidence: 99%
“…In order to obtain the most probable low energy conformations and the conformational space of each CTD sequence, we applied PCA using Cartesian coordinates. PCA is a widely used dimensionality reduction method to represent high-dimensional conformational information into two-dimensional plots to visualize the conformational space that the simulations sampled. , , PCA of conformations will also provide information about the convergence of the simulations as the energy landscapes should be connected in converged simulations. It is expected to observe a broad free energy landscape from the PCA of IDPs as they span large conformational ensembles compared to structured proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, several studies also point out that the ff14SB force field overestimates the helix formation due to the usage of globular protein structures in the parameterization. 39,59,60 On the other hand, ff14IDPSFF is relatively recent within the set of force fields that attempt to include the IDP flexibility by adding and optimizing the CMAP correction terms in the potential energy function of ff14SB. After studying short peptides and RNA-binding protein HIV-1 Rev, Duong et al 59 concluded that the ff14IDPSFF force field promotes random coil conformations and disordered secondary structures, which is consistent with experiments.…”
Section: Discussionmentioning
confidence: 99%